Thriving in leadership : strategies for making a difference in Christian higher education - Longman, Karen (Abilene Christian University Press, 2012)
In this book, seventeen senior leaders from Christian colleges and universities across the United States--collectively bringing with them hundreds of years of leadership experience--share fresh insights into the theory and practice of Christian higher education leadership. These authors speak honestly about the successes, failures, and demands that have shaped their current leadership decisions and their visions for the future.